Keefektifan Layanan Informasi via Jejaring Sosial Instagram terhadap Aktualisasi Diri Peserta Didik - Melenia Ayu Saputri; Lutfi Fauzan; Rizka Apriani; Melenia Ayu Saputri; Lutfi Fauzan (Universitas Negeri Malang, 2022)
Abstract: The study was conducted to determine the effectiveness of information services via Instagram on the self-actualization of students and whether there are differences in the level of self-actualization between two groups with different treatments. The implementation at SMP Negeri 6 Malang used two samples, class VIII (B) as an experimental class and VIII (D) as a control class with 32 students each. Experimental classes, treatment through Instagram and control classes conventionally use power points. The implementation started on March 22 - April 19, 2022, with seven treatments and no sample withdrawals. Research method with true experimental with pretest-posttest control group design. Hypothesis test with independent sample test through SPSS 22 to find out the comparison of experimental and control class scores. The pretest output in the experimental class has a mean of 84.72 and a posttest of 99.59. The control class at the pretest has a mean of 88.19 and a post-test of 93.63. The results of the independent sample test on the pretest have a value of F (0.442) with a significance (2-tailed) of 0.137 greater than 0.05 which means that there is no noticeable difference, then at the time of post-test it shows a value of F (1.028) with a significance (2-tailed) of 0.003 less than 0.05, so there is a striking difference between the level of self-actualization of the experimental and control classes. Abstrak: Penelitian dilakukan untuk mengetahui efektivitas layanan informasi via instagram terhadap aktualisasi diri peserta didik dan ada tidaknya perbedaan tingkat aktualisasi diri antara dua kelompok dengan perlakukan yang berbeda. Pelaksanaan di SMP Negeri 6 Malang dengan memakai dua sampel, kelas VIII (B) sebagai kelas eksperimen dan VIII (D) sebagai kelas kontrol dengan masing-masing 32 peserta didik. Kelas eksperimen, treatment melalui instagram dan kelas kontrol secara konvensional menggunakan power point. Pelaksanaan mulai tanggal 22 Maret - 19 April 2022 dengan tujuh kali treatment dan tidak ada sampel yang gugur. Metode penelitian dengan true experimental dengan pretest-posttest control group design. Uji Hipotesis dengan independent sample test melalui SPSS 22 untuk mengetahui perbandingan skor kelas eksperimen dan kontrol. Output pretest pada kelas eksperimen memiliki mean 84.72 dan posttest 99.59. Kelas kontrol saat pretest memiliki mean 88.19 dan posttest 93.63. Hasil uji independent sample test pada pretest memiliki nilai F (0.442) dengan signifikansi (2-tailed) 0.137 lebih besar dari 0.05 yang berarti tidak adanya perbedaan yang mencolok, kemudian pada saat posttest menunjukkan nilai F (1.028) dengan signifikansi (2-tailed) 0.003 lebih kecil dari 0.05, sehingga ada perbedaan yang mencolok antara tingkat aktualisasi diri kelas eksperimen dan kontrol.